Hydroxocobalamin Treatment and Pediatric Migraine Disability Assessment Scale Scores - Ayça, Senem; Dogan, Ceren (Journal of Pediatric Neurology, 2022)
Migraine is a common neurologic disorder in children, especially in adolescents. It can affect the school performance, family, and social daily activities. The Pediatric Migraine Disability Assessment Scale (PedMIDAS) is commonly used in young patients. This study evaluated vitamin B12 deficiency in children with migraine and the effect of hydroxocobalamin treatment on PedMIDAS scores. The study group comprised patients with vitamin B12 deficiency and diagnosed migraine. The PedMIDAS questionnaire was conducted before and 3 months after hydroxocobalamin treatment. PedMIDAS scores were evaluated and compared before and after hydroxocobalamin treatment. The mean ± standard deviation of vitamin B12 level was 175.9 ± 21.3 pg/mL in children with migraine. The PedMIDAS scores were significantly lower after hydroxocobalamin treatment than before treatment (p < 0.001). These results indicated that hydroxocobalamin made a positive contribution to the mitigation of migraine symptoms in children and that treating vitamin B12 deficiency could be a useful option.
Keywords: childhood migraine; PedMIDAS; vitamin B12